Towards a framework for not‐for‐profit accounting* - FALK, HAIM (Contemporary Accounting Research, 1992)
This paper analyses the theoretical explanations for the not‐for‐profit ( nfp ) organization phenomenon, distinguishes between those organizations and profit entities, clusters NFPs on two dimensions, and suggests an accounting framework that is consistent with both the economic nature of NFPs and the nature of the giving decision. Résumé. L'auteur analyse les explications théoriques du phénomène de constitution d'organismes sans but lucratif (OSBL), établit la distinction entire ces organismes et les entreprises à but lucratif, regroupe les OSBL sous deux aspects différents, et suggère une grille comptable adaptée à la nature économique des OSBL ainsi qu'à la teneur du choix philanthropique.